2013
DOI: 10.2175/106143012x13560205144614
|View full text |Cite
|
Sign up to set email alerts
|

Year‐Round Atmospheric Wet and Dry Deposition of Nitrogen and Phosphorus on Water and Land Surfaces in Nanjing, China

Abstract: The dry deposition of ammonium, nitrate, and total phosphorus (TP) to both water (DW) and land (DD) surfaces, along with wet deposition, were simultaneously monitored from March 2009 to February 2011 in Nanjing, China. Results showed that wet deposition of total phosphorus was 1.1 kg phosphorus ha (-1)yr(-1), and inorganic nitrogen was 28.7 kg nitrogen ha (-1)yr(-1), with 43% being ammonium nitrogen. Dry deposition of ammonium, nitrate, and total phosphorus, measured by the DW/DD method, was 7.5/2.2 kg nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Atmospheric wet P deposition in Chinese terrestrial ecosystems was approximately 0.21 kg P ha −1 a −1 . Previous studies have reported P deposition only from scattered sites; e.g., Luo et al [] reported that wet P deposition was about 0.33 kg P ha −1 a −1 in Lake Taihu, while Sun et al [] reported rates of 1.1 kg P ha −1 a −1 in Nanjing. Other studies in different parts of the world also have recorded levels of atmospheric wet P deposition around 0.028–0.7 kg P ha −1 a −1 (Table ) [ He et al , ; Herut et al , ; Koelliker et al , ; Morales et al , ; Parron et al , ; Pollman et al , ; Rolff et al , ; Tsukuda et al , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric wet P deposition in Chinese terrestrial ecosystems was approximately 0.21 kg P ha −1 a −1 . Previous studies have reported P deposition only from scattered sites; e.g., Luo et al [] reported that wet P deposition was about 0.33 kg P ha −1 a −1 in Lake Taihu, while Sun et al [] reported rates of 1.1 kg P ha −1 a −1 in Nanjing. Other studies in different parts of the world also have recorded levels of atmospheric wet P deposition around 0.028–0.7 kg P ha −1 a −1 (Table ) [ He et al , ; Herut et al , ; Koelliker et al , ; Morales et al , ; Parron et al , ; Pollman et al , ; Rolff et al , ; Tsukuda et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Vet et al [] estimated that with the exception of the driest areas (MAP < 40 cm) in the world (including southwest North America, southwest South America, and southwest and northern Africa), there are roughly equal contributions of dry and wet N deposition (i.e., 50% ± 10%) at continental scales (including China). Similarly, it was estimated that dry P deposition contributed 40–75% of the total atmospheric P deposition [ Hou et al , ; Luo et al , ; Sun et al , ]. Therefore, we assumed that the N:P ratios of total deposition (including wet and dry deposition) still remain at a high level, resulting from high N deposition and low P deposition [ Peñuelas et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of aerosols was set at 50 µg/m 3 through the adjustment of a flux valve, while the value of Nanjing city was 43-74 µg/m 3 in 2014-2016 [50]. The nitrogen levels were 0, 15 (half dose), 30 (background dose), and 60 (double dose) kg N hm −2 year −1 (32 plants were needed for each species), while bulk deposition fluxes of inorganic nitrogen averaged 35.8 kg N hm −2 year −1 , and wet deposition fluxes of inorganic nitrogen were 28.7 kg N hm −2 year −1 [51]. In order to maintain the uniformity of carbon dioxide and temperature, the control was fumigated using pure water vapor, to ensure the uniformity of environmental factors (such as temperature, CO 2 concentration, etc.)…”
Section: Experimental Designmentioning
confidence: 99%
“…The deposition of pollutants in the air to water body is also another concern of environmental fate and transport. Sun et al (2013) studied the dry deposition of ammonium, nitrate, and total phosphorus (TP) to both water (DW) and land (DD) surfaces, along with wet deposition, from March 2009 to February 2011 in Nanjing, China. Results showed that significant differences between the DW and DD methods.…”
Section: Environmental Fate and Transportmentioning
confidence: 99%